Essential Oil Constituents and Yields from Leaves of Blepharocalyx salicifolius (Kunt) O. Berg and Myracrodruon urundeuva (Allemão) Collected during Daytime - Olívia Bueno da Costa; Cláudio Henrique Soares Del Menezzi; Luiz Eduardo Celino Benedito; Inês Sabioni Resck; Roberto Fontes Vieira; Humberto Ribeiro Bizzo (International Journal of Forestry Research)
The purpose of this study was to evaluate the essential oil composition and yield from leaves of two Brazilian species (Myracrodruon urundeuva and Blepharocalyx salicifolius) harvested during daytime. Essential oils were obtained by steam distillation and had their yield determined. Blepharocalyx salicifolius presented yields of 0.049% (9 a.m.), 0.045% (1 p.m.), and 0.069% (5 p.m.). For Myracrodruon urundeuva, we found 0.13% (9 a.m.), 0.11% (1 p.m.), and 0.08% (5 p.m.). Finally, compound identification and quantification were carried out by GC-MS and GC-FID techniques, respectively. Thirteen major compounds were identified for Blepharocalyx salicifolius, representing 91.6% of the EOs, of which p-cymene (25.9%) was detected as amajor component. Nine major compounds were identified for Myracrodruon urundeuva, representing 90.3% of the EOs, whereas β-myrcene showed the greatest concentration (66.4%).